Management of the Axilla in the Era of Breast Cancer Heterogeneity - de Meric de Bellefon, Maïlys; Lemanski, Claire; Ducteil, Angélique; Fenoglietto, Pascal; Azria, David; Bourgier, Celine (Frontiers in Oncology, 2018)
Systemic therapies take into account breast cancer heterogeneity by tailoring specific pathway involved in some breast cancer subtypes. At the opposite, breast cancer intrinsic radiosensitivity is poorly understood and studied. Hence, radiotherapy personalization in breast cancer is still pending. In this review, we will summarize existing data about axillary nodes management, impact of breast cancer radiotherapy on axilla management, indications of axilla irradiation and predictive biomarkers of patients’ outcome (tumor control and late toxicities) after axilla irradiation.